GENERAL DIDACTICS AND METHODS OF TEACHING MOTHER TONGUE - Nisanbaeva Akmaral Kaldibaevna (European Journal of Humanities and Educational Advancements, 2023)
This article contains thoughts and comments about the general didactic and methods of teaching the mother tongue. The mother tongue, often referred to as the native language, holds a significant place in an individual’s identity, culture, and cognitive development. Teaching the mother tongue effectively is essential in preserving linguistic heritage and fostering a deep understanding of cultural roots. Language is the primary tool for communication, cognitive development, and cultural expression